Dynamic changes in mental health status related to the COVID-19 pandemic among health care workers and inpatients in China - Tong, Yujun; Zhang, Qian; Wang, Xiaoran; Du, Yanlin; Chang, Dong; Cui, Yong; Duan, Xinchun (Frontiers in Psychiatry, 2022)
Background: Exposure to Coronavirus Disease 2019 (COVID-19) can cause severe mental health problems, the dynamics of which remain unclear. This study evaluated the mental status of frontline healthcare workers (FHWs) and suspected infected patients (SIPs) during different periods of the COVID-19 outbreak. Methods: Demographic and psychological data were collected through a cross-sectional survey of 409 participants in a hospital from January 20, 2020, to August 7, 2020. Acute psychological disorders (APDs) including symptoms of anxiety and depression, were assessed using the Zung Self-Rating Anxiety/Depression Scale (SAS/SDS). Results: A total of 206 FHWs and 203 SIPs completed the electronic questionnaire. Overall, the prevalence rates of anxiety and depression among SIPs were 3.9% and 19.4%, respectively, while significantly higher prevalence rates (17.7% and 25.1%) were found among FHWs, P-value < 0.05. The psychological status among SIPs did not differ significantly across the three periods. The FHWs were more vulnerable, as their SAS and SDS scores and almost all the dimensions scales were significantly higher during the local epidemic period than during the national outbreak and sporadic periods (all P-values < 0.001). The prevalence of anxiety (34.41%) and depression (41.94%) was significantly higher during the local epidemic period (P<0.001). The logistic and linear mixed models showed that age, sex and doctor-patient ratio independently influenced the scores of most dimensions (P<0.05). Conclusion: Compared to the COVID-19 pandemic at the national level, the local epidemic had a greater influence on FHWs’ mental health. More attention should be paid to the workload of FHWs.